Exploring green finance, intellectual capital, and firm size's impact on firm value - Agustina, Dela; Ramadania, Ramadania; Wendy, Wendy; Giriati, Giriati; Mustaruddin, Mustaruddin (Junal Ilmu Manajemen, 2025)
This study aims to examine the impact of green finance, intellectual capital, and firm size on corporate value, utilizing financial performance as a mediating variable. The research is centered on companies listed in the Kompas 100 Index from 2020 to 2023, involving a sample of 50 firms. The analytical approach employed is panel data regression using the Random Effect Model, supplemented by the Sobel test to evaluate mediation effects. The results indicate that green finance, intellectual capital, and firm size positively and significantly affect financial performance. Furthermore, both green finance and intellectual capital significantly influence firm value, although green finance demonstrates a negative coefficient. The size of the firm and its financial results do not significantly impact its overall value. The Sobel test demonstrates that financial performance serves as a significant mediating factor in the relationship between the three independent variables and the firm's value. In summary, the research model explains 19.8% of the variation in firm value. These findings have important implications for developing corporate strategies aimed at increasing firm value through the cohesive management of environmental factors, intellectual capital, and financial performance.